Tightrope life - Oliveira, Renata Couto de Azevedo de (2021)
The image created for this edition is a digital collage that shows a small tightrope walker walking on a rope from which there are hanging images that refer to the literary examples used in the articles of the so-called “Verse, prose, drama and fiction: literature and organizations”. The inspiration came from string literature, a genre that combines literature and art and whose booklets are usually tied to a string with pegs. The chimneys between which the rope extends are from the Battersea thermoelectric power plant in London (United Kingdom), which is now defunct. The image of the plant has sentimental value and is part of popular culture. It is she who appears on the cover of the album “Animals”, by the English band Pink Floyd. It seems that the pig floating between the towers of the plant on the cover of the album, originally conceived by the band's guitarist, Roger Waters, refers to the literary classic “The Animal Revolution”, by also Englishman George Orwell. Both the album and the book criticize political systems and social conditions at different times in history.